Designing a Self-Perception Cognitive Questionnaire for Italian Multiple Sclerosis Patients (Sclerosi Multipla Autovalutazione Cognitiva, SMAC). A Preliminary Exploratory Pilot Study - Riccardi, Alice; Ognibene, Francesca; Mondini, Sara; Nucci, Massimo; Margoni, Monica; Meglioranzi, Ilaria; Carta, Elisa; Zywicki, Sofia; Miante, Silvia; Perini, Paola; Rinaldi, Francesca; Puthenparampil, Marco; et al. (Frontiers in Neurology, 2021)
Background. Although cognition in Multiple Sclerosis (MS) is assessed by several neuropsychological tests, only a few tools exist to investigate patients’ perspective on cognitive functioning. Objective. To develop a new questionnaire aimed at exploring the self-perception on cognition in Italian MS patients. Methods. 120 Relapsing-Remitting MS (RRMS) patients and 120 matched Healthy Controls (HC) completed a 25-item-based questionnaire named Sclerosi Multipla Autovalutazione Cognitiva (SMAC). The Symbol Digit Modalities Test (SDMT), the Delis-Kaplan Executive Function System Sorting Test (D-KEFS ST), the Beck Depression Inventory (BDI-II) and the Fatigue Scale (FSS) were also administered to the patients. Results. Significantly higher SMAC scores were displayed by RRMS patients compared to HC (30.1±16.9 vs 23.4±10.4, p=0.003). SMAC inversely correlated with SDMT (r=-0.31, p<0.001), D-KEFS ST FSC (r=-0.21, p=0.017), D-KEFS ST FSD (r=-0.22, p=0.015) and D-KEFS ST SR (r=-0.19, p=0.035) and positively correlated with FSS (r=0.42, p<0.001) and BDI-II (r=0.59, p<0.001). Cronbach’s alpha coefficient for the questionnaire was 0.94. Conclusion. Preliminary findings suggest SMAC as a promising Patient-Reported Outcome to be included in MS neuropsychological evaluation, thus warrants to be further tested and developed.